The coupling and competition of crystallization and phase separation, correlating thermodynamics and kinetics in OPV morphology and performances - Zaiyu Wang (Nature Portfolio, 2021)
Designing efficient blue perovskite LEDs by using mixed halides perovskite is still a challenge, limited mainly by the phase segregation issue. Here, the authors demonstrate in situ fabrication of quasi-2D CsPbClBr2 nanocrystal films with mixed ligands to overcome the constraint.